2018
DOI: 10.1007/5584_2018_263
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of Humoral Immunity in Children with IgG Subclass Deficiency and Recurrent Respiratory Infections

Abstract: Respiratory tract infections in children are one of the most common causes for medical consultations. When the infections are of recurring nature, they are a major reason for the diagnostics for primary immunodeficiency that is in about 65% of cases underlain by disorders of humoral immunity. This study seeks to retrospectively evaluate the history of recurrent respiratory tract infections in children with humoral disorders and the associations among deficiencies in the immune system components. We evaluated 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Only one case of agammaglobulinemia has been recorded, in a 3-year old boy. In order to confirm that a child has humoral immunodeficiency, it is necessary to eliminate certain nephrotic symptoms and protein-losing enteropathies, hematological malignancies, and also the use of certain drugs, in particular immunosuppressants [28]. In our case, the only information we could retain about the child is that he has diffuse interstitial lung disease.…”
Section: Resultsmentioning
confidence: 95%
“…Only one case of agammaglobulinemia has been recorded, in a 3-year old boy. In order to confirm that a child has humoral immunodeficiency, it is necessary to eliminate certain nephrotic symptoms and protein-losing enteropathies, hematological malignancies, and also the use of certain drugs, in particular immunosuppressants [28]. In our case, the only information we could retain about the child is that he has diffuse interstitial lung disease.…”
Section: Resultsmentioning
confidence: 95%
“…The infections are frequently prolonged and recurrent with numerous contributing bacteria, especially Streptococcus pneumoniae, Haemophilus influenzae, and Staphylococcus, but also atypical and opportunistic ones such as Mycoplasma or Pseudomonas aeruginosa [41]. Infections may result from an impaired immune response to vaccination noted in IgA-deficient children and adults who have been administered an unconjugated polyvalent pneumococcal vaccine [43]. IgA deficiency lower than 0.007 g/l is an established risk factor for the incidence of pneumonia and may predispose affected individuals to pneumococcal infections of the RT, and it also implies rhinosinusitis and tonsillitis [44].…”
Section: Clinical Phenotypes In Iga Deficiencymentioning
confidence: 99%
“…A recent retrospective study has shown that immunoglobulin deficiencies are affecting different isotypes. Thus, RTIs in children determine abnormal levels of IgG, and also of IgA and IgM (Pasternak et al, 2018). When studying cytokine secretion in RTI occurred in children decreased levels of proinflammatory cytokines were found, mainly IFN-gamma, indicating the increased risk for developing RTI.…”
Section: Introductionmentioning
confidence: 99%